The isolation of alkaloid from the leaves of Samanea saman (Jacq.) Merr. (Leguminosae) - Carluen, Abelen B.
An alkaloid was isolated from the leaves of Samanea saman (Jacq.) Merr. (Leguminosae) or acacia leaves which were obtained from UP Diliman Campus. The alkaloid was extracted with chloroform. The chloroform extracts were chromatographed on different solvent systems, one of which was butanol-acetic acid-water or BAW with the ratio of 3:1:1.